Chronic hepatitis B associated with hepatic steatosis, insulin resistance, necroinflammation and fibrosis - Yilmaz, Bulent (Afr Health Sci, 2015)
BACKGROUND: The effect of hepatitis B virus (HBV) infection on fatty liver disease is unclear. OBJECTIVES: The aim of this study was to investigate the viral and host causes of fatty liver in chronic hepatitis B (CHB) patients. This study included 88 CHB patients of which 17 were not treated. Liver biopsy was performed in each patient. Group 1 included those with hepatic steatosis (n=28) and group 2 those without hepatic steatosis. The groups were compared in terms of age, body mass index (BMI), Homeostasis Model Assessment- Insulin Resistance (HOMA-IR), viral load, biochemical parameters and histological findings. Patients in group 1 were subdivided according to the degree of steatosis as follows: grade 1 (15 patients, 53.6%), grade 2 (6 patients, 21.4%), and grade 3 (7 patients, 25%). RESULTS: In group 1 (n=28), mean age, BMI, cholesterol, and HOMA-IR were found to be significantly higher than in group 2 (n=60). There were no significant differences in the positivity of viral load, HbeAg, treatment, fibrosis and other laboratory parameters between the two groups. HOMA-IR was the only independent predictive factor of liver steatosis in patients with CHB in logistic regression analysis. CONCLUSION: Hepatic steatosis in CHB patients was associated with host metabolic factors.